2014
DOI: 10.1111/jmg.12107
|View full text |Cite
|
Sign up to set email alerts
|

Reworking of the Gangdese magmatic arc, southeastern Tibet: post‐collisional metamorphism and anatexis

Abstract: The Gangdese magmatic arc, southeastern Tibet, was built by mantle-derived magma accretion and juvenile crustal growth during the Mesozoic to Early Cenozoic northward subduction of the Neo-Tethyan oceanic slab beneath the Eurasian continent. The petrological and geochronological data reveal that the lower crust of the southeastern Gangdese arc experienced Oligocene reworking by metamorphism, anatexis and magmatism after the India and Asia collision. The post-collisional metamorphic and migmatitic rocks formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 118 publications
1
34
0
Order By: Relevance
“…Since zircons crystallized earlier than garnet (which formed during the granulite facies stage), this also explains why the zircons do not show garneteffect in chondrite-normalized REE patterns. Similar cases have been described in previous studies from different terranes (Berger et al, 2008;Zandt et al, 2004;Zhang et al, 2013Zhang et al, , 2014b2015aand, 2015bZhao et al, 2014a). We thus favor thee second possibility and the age of 440 Ma is interpreted to represent the time of granulite facies metamorphism while the age of magmatism would be slightly older than this.…”
Section: Magmatic and Metamorphic Geochronologysupporting
confidence: 57%
See 3 more Smart Citations
“…Since zircons crystallized earlier than garnet (which formed during the granulite facies stage), this also explains why the zircons do not show garneteffect in chondrite-normalized REE patterns. Similar cases have been described in previous studies from different terranes (Berger et al, 2008;Zandt et al, 2004;Zhang et al, 2013Zhang et al, , 2014b2015aand, 2015bZhao et al, 2014a). We thus favor thee second possibility and the age of 440 Ma is interpreted to represent the time of granulite facies metamorphism while the age of magmatism would be slightly older than this.…”
Section: Magmatic and Metamorphic Geochronologysupporting
confidence: 57%
“…2) (Kong et al, 1995;Zhejiang, 1989;Lan et al, 1995a and1995b). These rock associations are typical of a continental shelf suite (Wang et al, 2013c;Zhao, 2014;Lan et al, 1995aLan et al, , 1995b and are similar to those reported from accretionary continental margins (Rao and Santosh, 2011;Zhang et al, 2013Zhang et al, , 2014b2015a and2015b). Kong et al (1995) divided the Chencai Group metasedimentary rocks into four formations which are (from the base upwards): the Daojiuwan Formation, Xiahetu Formation, Xiawuzhai Formation and Xu'an Formation (Fig.…”
Section: Geological Backgroundmentioning
confidence: 62%
See 2 more Smart Citations
“…The South Lhasa terrane consists of the high-grade metamorphic sequence (Nyingchi Complex), Carboniferous−Triassic strata and 165-22 Ma granitoids and mafic rocks (Booth et al, 2009;Burg et al, 1997;Dong et al, 2010a;Geng et al, 2006; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 2011Zhang et al, 2010aZhang et al, , 2013. The Nyingchi Complex is a tectonic mélange and mainly consists of schists, migmatite, orthogneisses, paragneisses and metasandstone, with minor quartzite, calc-silicate rocks, marble and granulite (Dong et al, 2010a;Guo et al, 2011Guo et al, , 2012Guo et al, , 2013Lin et al, 2013a;Zhang et al, 2008Zhang et al, , 2010bZhang et al, , 2013Zhang et al, , 2015. Due to the lack of detailed geological and geochemical investigation, the age and origin of the protoliths of the metamorphic rocks from the Nyingchi Complex have not yet been well documented.…”
Section: Accepted Manuscriptmentioning
confidence: 95%